PENERAPAN IPTEK PADA USAHA MIKRO MINYAK KELAPA TRADISIONAL - Suardana, NPG; Janardana, IGN; Swara, IWY (Buletin Udayana Mengabdi, 2018)
Micro business of traditional palm oil is still run by some families in Banjar Pagutan Banjarangkan Village, Banjarangkan District, Klungkung Regency–Bali. This business is a traditional business which has been run through generations with standardized method. Although this oil has been replaced by modern industrial-made oils and the price is cheaper, but this product has specific customers, the Balinese rice sellers who need it to cook savory food with typical aroma. The product is marketed around Banjarangkan Village. The problems faced by the entrepreneur are related to time and human resource efficiency which affect the product price. Those problems are caused by the squeezing process of coconut milk that still uses human resource, so it takes more resources and longer time. Based on the above explanation, the purpose and outcome of this designed-activity are to produce integrated squeezer and grater machine, to improve the human resources skill in operating machine and teach about marketing and product management. This social-service activity which included designing machine, manufacturing machine, feasibility test machine, technical assistance to the partner in which the team of social-service got some feedbacks from the business group partner related to the process conducted to improve the time efficiency, product marketing management, demonstration and training of using the machine.